Comparative evaluation of the shear strength of orthodontic adhesives for ﬁxation of brackets - H. Almokaddam; N. S. Tuturov; I. Katbeh; A. Saleh (Эндодонтия Today)
INTRODUCTION. Over the past decades, there has been signiﬁcant growth in adhesive technologies for ﬁxed orthodontic appliances. Developments in adhesive systems have focused on simpliﬁed methods of use, improved composition and high bonding ability to tooth structure.AIM. The aim of this study is to compare the shear bond strength of a 5th generation adhesive system and a universal adhesive system in two etching techniques for ﬁxation of metal brackets.MATERIALS AND METHODS. The study consisted sample of 30 removed human upper premolars. The teeth were randomly distributed into three groups, 10 in each group. In the group 1, the Transbond XT adhesive system (3M Unitek) was used, in the group 2 – the universal adhesive Tetric N bond Universal (Vivapen) in the etching technique, in the group 3 – Tetric N bond Universal (Vivapen) in the self-etching technique. The study used metal brackets for upper premolars Gemini Bracket MBT (3M Unitek, USA) with a micro-engraved base with an area of 10.61 mm.RESULTS. In group 1, the shear strength value was 21.2 ± 3.2 MPa, in group 2 – 21.6 ± 5.2 MPa, in group 3 – 17.7 ± 6.4 MPa. There were no statistically signiﬁcant diﬀerences between the study groups. According to the study, a decrease in the level of adhesive force was found when using a universal adhesive without prior etching of the enamel with phosphoric acid. However, this level remained within the clinically recommended range.CONCLUSIONS. Thus, all studied adhesive systems used in various etching techniques demonstrated high adhesive performance, providing strong adhesion of the orthodontic structure to the tooth surface.